Sodium bicarbonate ingestion mitigates the heat-induced hyperventilation and reduction in cerebral blood velocity during exercise in the heat - Katagiri, A.; Kitadai, Y.; Miura, A.; Fukuba, Y.; Fujii, N.; Nishiyasu, T.; Tsuji, B. (Journal of Applied Physiology, 2021)
Hyperthermia during exercise in the heat causes minute ventilation (VE) to increase, which leads to reductions in arterial CO2 partial pressure (PaCO2) and cerebral blood flow. On the other hand, sodium bicarbonate ingestion reportedly results in metabolic alkalosis, leading to decreased VE and increased PaCO2 during prolonged exercise in a thermoneutral environment. Here, we investigated whether sodium bicarbonate ingestion suppresses heat-induced hyperventilation and the resultant hypocapnia and cerebral hypoperfusion during prolonged exercise in the heat. Eleven healthy men ingested a solution of sodium bicarbonate (0.3 g/kg body wt) (NaHCO3 trial) or sodium chloride (0.208 g/kg) (NaCl trial). Ninety minutes after the ingestion, the subjects performed a cycle exercise for 60 min at 50% of peak oxygen uptake in the heat (35°C and 40% relative humidity). Esophageal temperature did not differ between the trials throughout (P = 0.56, main effect of trial). VE gradually increased with exercise duration in the NaCl trial, but the increases in VE were attenuated in the NaHCO3 trial (P = 0.01, main effect of trial). Correspondingly, estimated PaCO2 and middle cerebral artery blood velocity (an index of anterior cerebral blood flow) were higher in the NaHCO3 than the NaCl trial (P = 0.002 and 0.04, main effects of trial). Ratings of perceived exertion were lower in the NaHCO3 than the NaCl trial (P = 0.02, main effect of trial). These results indicate that sodium bicarbonate ingestion mitigates heat-induced hyperventilation and reductions in PaCO2 and cerebral blood velocity during prolonged exercise in the heat.